MATH SOLVE

3 months ago

Q:
# What is(y^4/3 x y^2/3)^-1/2

Accepted Solution

A:

[tex]\bf \left( y^{\frac{4}{3}}xy^{\frac{2}{3}} \right)^{-\frac{1}{2}}\implies \left( y^{\frac{4}{3}}y^{\frac{2}{3}}x \right)^{-\frac{1}{2}}\implies \left( y^{\frac{4}{3}+\frac{2}{3}}x \right)^{-\frac{1}{2}}\implies \left( y^{\frac{6}{3}}x \right)^{-\frac{1}{2}} \\\\\\ (y^2x^1)^{-\frac{1}{2}}\implies \left( y^{-\frac{1}{2}\cdot 2}x^{-\frac{1}{2}\cdot 1} \right)\implies y^{-1}x^{-\frac{1}{2}}\implies \cfrac{1}{y}\cdot \cfrac{1}{x^{\frac{1}{2}}}\implies \cfrac{1}{y\sqrt{x}}[/tex]